Identification of Causes of Red Leaf Spot on Red Jabon (Anthocephalus macrophyllus (Roxb.) Havil) Seeds in Kima Atas Permanent Nursery, Manado Forestry Research Institute (Identifikasi Penyebab Penyakit Bercak Merah Pada Bibit Jabon Merah (Anthocephalus Macrophyllus (Roxb.) Havil) di Persemaian Permanen Kima Atas, Balai Penelitian Kehutanan Manado) - Hanif Nurul Hidayah; Illa Anggraeni (Jurnal Wasian, 2015)
Fulfillment the needs of Red Jabon (Anthocephalus macrophyllus (Roxb.) Havil) seeds on the other hand can create an unbalanced ecosystem. The availability of red Jabon seed was becoming a source of food for pests, then it causes an explosion of pests and pathogens. The disease that most often affect red Jabon seeds, both in the nursery and in the field was red leaf spot (antraknose). The initial step to control red leaf spot disease is the identification of causing. Identification method performed by observation of the symptoms in the field, followed by microscopic observation in a laboratory. Based on the identification result, it was known that the disease caused by the fungus Cercospora sp., Colletotrichum sp. and Pestalotia sp. The effect caused by those fungal pathogens was the disruption of the photosynthetic process that ultimately inhibits the growth of red Jabon seeds. The controls which have been done are arranged the watering intensity, isolated the infected seed,and  applied the chemical fungicide.